Biological Assessment of Anthropogenic Impacts in Buguma Creek, Rivers State, Nigeria - Chris, Davies Ibienebo; Anyanwu, Emeka Donald (Journal Omni-Akuatika, 2023)
The objective of this research was to assess the anthropogenic impact on plankton and macrobenthic fauna composition, abundance, distribution, and diversity of four communities in Buguma creek. The Phytoplankton, zooplankton, and benthic fauna samples were collected quantitatively monthly from each of the four sampling stations between January and June 2020 using standard sampling methods. Margalef (D), Shannon Wienner (H), and Evenness indices were used to determine species richness and diversity respectively using the PAST statistical package. This study revealed that artisanal refinery activities, sand mining/dredging, and discharge of industrial, domestic, human, and animal wastes have adversely affected the aquatic biota (plankton and macrobenthic fauna) in Buguma creek. The effects of these activities have remarkable spatial manifestations; with the more perturbed especially station 2, having a lower number of species and abundance. The preponderance of indicator species is a confirmation while the community structure gave an insight into the negative impact of these activities individually and cumulatively. The brunt of these activities rests more on the macrobenthic fauna; probably due to their unique characteristics and position in the aquatic environment. The result indicated that Buguma creek had been polluted seriously to a large extent. Keywords: Aquatic biota, Bioindicator, Anthropogenic, Artisanal refinery, Diversity